INNOVATION DEVELOPMENT AND TECHNOLOGY ADVANCEMENTS IMPACT ON MSME SUCCESS WITH DIGITAL MARKETING LITERACY AS A INTERVENING - Eka Febrianti, Silvia; Wardana, Ludi Wishnu; Nasikh (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: Companies around the world invest heavily in innovation and technology development strategies to improve their competitiveness. However, Micro, Small and Medium Enterprises (MSMEs) in Malang Regency still face challenges in adopting digital technology and developing innovations to achieve business success. Purpose: This study aims to analyze the influence of innovation development strategies and technological advances on the success of MSME businesses in Malang Regency, with digital marketing literacy as a mediating variable. Novelty: This study provides new insights into the mediation role of digital marketing literacy in the relationship between innovation development strategies, technological advancements, and MSME business success. These findings can make theoretical and practical contributions that are useful for the development of MSMEs in the digital era. Research Methods: This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to MSME owners or managers in Malang Regency. Data analysis uses structural equation modeling (SEM) to test the research hypothesis. Results: The results of the study show that the strategy of developing innovation and technological advances has a positive and significant effect on the success of MSME businesses. In addition, digital marketing literacy has been proven to mediate the relationship between the two variables. Research Contributions: This research makes a theoretical contribution by expanding the understanding of the mediation role of digital marketing literacy in increasing the success of MSME businesses through innovation development strategies and technological advancements.